Lycium barbarum polysaccharides alleviate LPS-induced inflammatory responses through PPARγ/MAPK/NF-κB pathway in bovine mammary epithelial cells - Xu, Tianle; Liu, Run; Lu, Xubin; Wu, Xinyue; Heneberg, Petr; Mao, Yongjiang; Jiang, Qianming; Loor, Juan; Yang, Zhangping (Journal of animal science, 2022)
UNLABELLED: As the main component of the Gram-negative bacterial cell wall, lipopolysaccharide (LPS) is well documented as an inducer of inflammation in bovine mammary cells. Lycium barbarum (goji) polysaccharides (LBP) have been used in nonruminants as prebiotics to improve growth performance, immune ability, and antioxidant capacity. We aimed to investigate the underlying effects of LBPs on proinflammatory responses in LPS-stimulated primary bovine mammary epithelial cells (bMECs). Cells were isolated from mammary tissue of three lactating Holstein cows without clinical disease (30.26 ± 3.1 kg/d of milk yield; 175 ± 6 DIM). For the pre-experimental treatment, bMECs were precultured with serum-free medium for 12 h. Treatments were as follows: pretreatment with culture medium devoid of LPS or LBP for 30 h (CON); CON for 24 h followed by challenge with 2 μg/mL LPS for 6 h (LPS); pretreatment with 100 or 300 μg/mL LBP for 24 h followed by LPS challenge (2 μg/mL) for 6 h (LBP(100)+LPS; LBP(300)+LPS). To further determine if the effect of LBP on immuneregulation is peroxisome proliferator-activated receptor-γ (PPARγ) activation dependent, an inhibitor of PPARγ, GW9662, at a concentration of 1 μM was used. Cells treated with LBP at 100, 300, and 500 μg/mL had upregulated protein abundance of PPARγ, while PGC1α had a higher expression only at 300 μg/mL of LBP treatment. Compared with CON, cells pretreated with LBP at 100 and 300 μg/mL had greater protein abundance of SCD1 and SREBP1. 5-Ethynyl-2'-deoxyuridine (EdU) staining and cell wound healing assays showed that the negative effect of LPS alone on cell proliferation was reversed by pretreatment with LBP at both 100 and 300 μg/mL. Upregulation of gene and protein abundance of proinflammatory factors and cytokines (COX-2, NLRP3, TNF-α, IL-1β, and IL-6) induced by LPS stimulation were alleviated by LBP pretreatment at 300 μg/mL (more than 2-fold decrease). Compared with LPS challenge alone, phosphorylation of proteins involved in NF-κB (IκBα and p65) and MAPK (p38, JNK, and ERK) pathways was downregulated following LBP treatment. Additionally, inhibition of PPARγ by GW9662 weakened the protective effect of LBP on LPS-induced protein abundance of phosphorylated p65, COX-2, IL-1β, and TNF-α. These results indicated that the protective effect of LBP on LPS-induced bMECs inflammatory responses is PPARγ activation-dependent. As such, this knowledge might help design strategies for intervening against the detrimental effects of bovine mastitis. INTERPRETIVE SUMMARY: Current research examined Lycium barbarum polysaccharides (LBP) for combating LPS-induced inflammatory responses in primary bovine mammary epithelial cells. We uncovered a preventive role of LBP in reducing detrimental effects induced by LPS including inhibition of NF-κB and MAPK along with peroxisome proliferator-activated receptor-γ (PPARγ) activation. The decrease in cell proliferation due to LPS was curtailed by pretreatment with LBP. Moreover, the effect of LBP on regulation of inflammatory responses in bovine mammary epithelial cell was PPARγ dependent. Collectively, data suggest that LBP reverses LPS-induced inflammatory response via MAPK/NF-κB signaling in a PPARγ-activation-dependent manner. Thus, the study provides new insights into therapeutic strategies for combating mastitis using LBP and highlighted the link between PPARγ and regulation of mammary cell inflammation.
Keywords: Cattle Diseases; Cattle; NF-κB signaling pathway; bovine mammary cells; epitelové buňky; Inflammation; PPARγ; mléčné žlázy zvířat; Lipopolysaccharides; laktace; NF-kappa B; Mammary Glands, Animal; PPAR gamma; kustovnice; inflammatory responses; ženské pohlaví; Lactation; Lycium barbarum polysaccharides; lipopolysacharidy; Epithelial Cells; nemoci skotu; Lycium; PPAR gama; zvířata; zánět; Animals; skot; Female